2015
DOI: 10.1210/jc.2015-2247
|View full text |Cite
|
Sign up to set email alerts
|

PTCSC3 Is Involved in Papillary Thyroid Carcinoma Development by ModulatingS100A4Gene Expression

Abstract: PTCSC3 downregulates S100A4, leading to a reduction in cell motility and invasiveness. We propose that PTCSC3 impacts PTC predisposition and carcinogenesis through the S100A4 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 31 publications
1
51
1
Order By: Relevance
“…The rs920778 C>T polymorphism leads to increased HOTAIR RNA expression, which might be the underlying mechanism in conferring PTC susceptibility. These data support the hypothesis that functional SNPs influencing lncRNA regulation may explain a part of PTC genetic basis171819.…”
Section: Discussionsupporting
confidence: 86%
“…The rs920778 C>T polymorphism leads to increased HOTAIR RNA expression, which might be the underlying mechanism in conferring PTC susceptibility. These data support the hypothesis that functional SNPs influencing lncRNA regulation may explain a part of PTC genetic basis171819.…”
Section: Discussionsupporting
confidence: 86%
“…Located in the promoter of a long non-coding RNA (lncRNA) gene named Papillary Thyroid Carcinoma Susceptibility Candidate 3 (PTCSC3), the risk allele of rs944289 impacts the expression of PTCSC3 by altering the binding affinity for the transcription factors C/EBPa and C/EBPb (10). PTCSC3 was shown to possess tumor suppressor properties by inhibiting the motility and invasion potential of PTC cells through the suppression of S100A4 transcription (11). The variant rs965513 at 9q22 is located in close vicinity of the Forkhead Box E1 (FOXE1) gene.…”
mentioning
confidence: 99%
“…S100A4 is not only a metastatic protein but also an oncoprotein that plays a critical role in the development of tumors. Depletion of S100A4 resulted in impaired proliferation and invasive capacity, including thyroid cancer [17,21,42], suggesting the importance of S100A4 in progressive phenotypes of cancers. Our in vitro study showed that targeting S100A4 in 8505C and Cal-62 cells decreases cell proliferation, invasion and migration and increases cell apoptosis.…”
Section: Potent Inhibitors Of Braf V600ementioning
confidence: 99%